Assessment of the greenhouse gas, Episodic air quality and public health benefits of fuel cell electrification of a major port complex. (15th April 2022) - Zhu, Shupeng; Kinnon, Michael Mac; Soukup, James; Paradise, Andre; Dabdub, Donald; Samuelsen, Scott
Abstract: Communities located adjacent to goods movement hubs (such as major ports) experience degraded air quality (AQ) because of emissions from on-road and off-road diesel equipment, including heavy-duty diesel trucks (HDDT), cargo, and materials handling equipment (CHE), ships, and rail technologies. In response, California is pursuing transitions to efficient and cleaner freight systems by introducing zero-emission technologies as the alternative to conventional technologies. Equipment and vehicles powered by hydrogen fuel cells represent a potential zero-emissions pathway for freight technologies at ports, including HDDT, CHE, ships, and rail applications, referred to collectively as fuel cell electric technologies (FCET). This work is the first to assess the AQ and human health impacts of deploying FCET to provide goods movement services at ports. Specific focus is given to southern California due to existing AQ challenges and the presence of significant activity from the San Pedro Bay Port Complex, which includes the Ports of Los Angeles and Long Beach. Sets of future vehicle and equipment cases are developed spanning a range of FCET penetrations and assessed to quantify how FCET provides improvements in primary and secondary pollutant concentrations and the value of corresponding public health benefits. If fuel cells are used in all technologies considered, the results show significant improvements in maximum 8-h ozone (−2.69 ppb to −5.09 ppb) and maximum 24-h PM2.5 (−0.59 μg/m 3 to −2.57 μg/m 3 ) can be achieved with FCET deployment, and the valuation of health benefits is estimated to range from $3.21 to $7.11 million per day depending on the level of penetration reached in each technology category. Reducing emissions from ships and HDDT is found to attain the highest health savings. Heightening the importance of these benefits, socioeconomically disadvantaged communities are found to experience larger health savings from FCET deployment in contrast to the population as a whole. As a co-benefit, FCET deployment is shown to result in greenhouse gas (GHG) emission reductions which will further increase with the sourcing of hydrogen from renewable sources. These findings demonstrate the importance of addressing environmental quality associated with the goods movement sector in urban areas and validate support of zero-emission projects through incentives and other policy mechanisms. Furthermore, policies designed to support zero-emission strategies within HDDT and ships powered by renewable fuels represent a promising pathway for air quality and GHG co-benefits. Graphical abstract: Image 1 Highlights: Fuel cell electrification at a port attains air quality improvements. Ocean going vessels and diesel trucks should be targeted first. Health benefits are valuable and improve environmental justice. GHG reductions are also sizeable if renewable hydrogen is used.